Seizures in patients with spinocerebellar ataxias: insights from a specialized institute in Peru - Abad, Alonso (2026)
Objective: To compare the frequency of seizures between patients with SCA10 and other SCA in a sample of the Peruvian population. Materials and methods: Observational study with a retrospective component through medical record review and a prospective component with interviews after prior informed consent. Patients with a genetic diagnosis of SCA attended between January 2014 and December 2023 in a national referral center in Peru were recruited. Results: We identified 125 cases from 87 families diagnosed with six types of SCA (SCA1, SCA2, MJD/SCA3, SCA6, SCA7 and SCA10), with an overall seizure frequency of 11.2%. Seizures predominated in the SCA10 subgroup (16%), contrasting with the other SCA subgroup (4%), which had only two cases of seizures in SCA2. Conclusions: Seizures are significantly more frequent in SCA10 compared to other SCA subgroup in the studied population. Tonic-clonic of unknown onset seizures are common in SCA10, while focal onset motor seizures were described in SCA2, most of them with good response with antiseizure medications.